1983
DOI: 10.1002/bip.360220317
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of amphipathic helices on analysis via matrix methods, with application to glucagon, secretin, and vasoactive intestinal peptide

Abstract: SynopsisA configuration partition function, which incorporates concepts embodied in the amphipathic helix hypothesis, has been formulated for a polypeptide in the presence of zwitterionic phospholipid. An enhanced probability is assigned to helix formation in any region of the polypeptide chain where side chains bearing charges of opposite sign will be situated on the same side of the a-helix but displaced from one another by one turn. This situation will arise when residues i -4 (or i -3) and i bear charges o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The extension of statistical mechanical theories of the helix-coil transition to include effects of lipids (Mattice & Robinson, 1981;Hamed et al, 1983) correctly predicts the increased helical content of sCT in the presence of lipids the presence and absence of DMPG: 90 µ peptide in 10 mM sodium phosphate buffer, pH 7.0 (X, ---), and in the presence of 2.4 mM DMPG ( , -). Points are the experimentally determined values, and lines are the least-squares best-fit curves for the mixtrues of secondary structures given in Table II.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The extension of statistical mechanical theories of the helix-coil transition to include effects of lipids (Mattice & Robinson, 1981;Hamed et al, 1983) correctly predicts the increased helical content of sCT in the presence of lipids the presence and absence of DMPG: 90 µ peptide in 10 mM sodium phosphate buffer, pH 7.0 (X, ---), and in the presence of 2.4 mM DMPG ( , -). Points are the experimentally determined values, and lines are the least-squares best-fit curves for the mixtrues of secondary structures given in Table II.…”
Section: Resultsmentioning
confidence: 86%
“…Calculation of Helix Probability Profiles. The probability of folding into a helical conformation was calculated for each amino acid residue by the method of Mattice and co-workers (Mattice & Robinson, 1981;Hamed et al, 1983). The statistical weights for each amino acid at 30 °C (Mattice & Robinson, 1981;Hamed et al, 1983) were used to construct a series of 3 X 3 matrices to calculate the helical content in water and SDS and to construct a series of 13 X 13 matrices for the conformation in zwitterionic lipids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that electrostatic interresidue interactions may play a role in stabilizing the helical structure of lipidbound segments of amphipathic helices~Segrest, 1977; Hamed et al, 1983!. Interresidue salt bridges formed between oppositely charged side chains three or four residues apart have been shown to stabilize a-helical structures by up to 6 kcal0mol0salt-bridgẽ Merutka & Stellwagen, 1991;Lyu et al, 1992!.…”
Section: Discussionmentioning
confidence: 99%
“…These latter conditions are convenient to study large molecules such as proteins and polypeptides but are completely inadequate in the case of small, flexible molecules like short peptides. It is well known, in fact, that in dilute aqueous solutions disordered populations are particularly favored, while the presence of ordered structures is negligible and, quite often, not detectable 20. On the other hand, conditions that mimic the hydrophobic environment typical of membranes may stabilize secondary structures; this is the reason why peptides are often studied in the presence of organic solvents and/or surfactants like sodium dodecylsulfate,21 even though the interpretation of the FTIR spectra becomes more complicated.…”
Section: Introductionmentioning
confidence: 99%